Pengaruh Kepemimpinan, Lingkungan Kerja Fisik dan Budaya Organisasi terhadap Kinerja Pegawai dengan Disipilin Sebagai Variabel Intervening pada Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari - Febriani, Yulita; Suryani, Arna; Akbar, Ali (Universitas Batanghari, 2025)
Employee performance is a vital part to support the success of an organization, including the Batang Hari Regency Library and Archives Service. This research aims to analyze the influence of leadership, physical work environment, and organizational culture on employee performance with discipline as an intervening variable. The research method uses a quantitative method by conducting a survey and distributing questionnaires to 51 ASN and Non-ASN employees. Data analysis in this study uses the SmartPLS 3.0 application to test the relationship between variables. The outcome of this research proves that the variables of leadership, physical work environment, and organizational culture have a positive effect on employee discipline. Discipline also has a significant effect on employee performance. In addition, leadership, physical work environment, and organizational culture directly or through discipline have a significant effect on employee performance. These results confirm that good leadership factors, a conducive work environment, and a good organizational culture can generate employee discipline, which will later have a positive effect on employee performance. Therefore, organizational managers must pay attention to factors that can increase employee productivity.